KONFLIK INTERNAL ANTARMASYARAKAT DUSUN BAGEK DEWA DAN MASYARAKAT DUSUN DAYEN RURUNG DI DESA KETARA KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Hidayanti, Sri (Humanis, 2014)
The conflict is a social process that customarily takes place in people's lives and is believed to be a main fact, whether in modern society and traditional society. So with that occurred in the community of the society Lombok exactly the hamlet community Bagek Dewa and the hamlet community of the Dayen Rurung, Ketara village. On the record of its history, conflicts inter the two hamlets has indeed been taking place since long ago and still continues to this day. The hereditary conflict can be said to be a feature of social relations in identifying inter society. The problem examined in this study are: how the historical background of the conflict, the factors that influence, as well as how solutions and constraints in the settlement. This research aims to study the historical background of the conflicts between the community and the factors that cause and solution and obstacles faced in the quest completion. The theory used is the trigger of conflict theory Simon Fisher, conflict theory of Ralf Dahrendorf and Lewis Alfred Coser, as well as Pierre Bourdieu's theory of violence. The analysis used in the study was qualitative with engineering data management through in-depth interviews and observations directly to the community as well as analysis of documents. Results of the study, namely the conflict hereditary intercommunity hamlet Bagek Dewa and the hamlet community of the Dayen Rurung in the Ketara village effected by a arid mountainous geographic conditions adjacent to the sea and the superiority of the genealogy, which claims the identity inter both communities. Factors that affect conflict, namely; historical factors, social, communication, economics, politics, law, the division of the territory. As for the solution of conflict reduction efforts as is by way of mediation, negotiation, and law proceedings (arbitration) and the constraints of lack of attention and efforts of the government in the follow-up to the two communities in conflict as well as the application of the law of function don’t maximum has a slash select sharply down and dulled up.
Keywords: internal conflicts, interhamlet, historical.